Pemeriksaan widal untuk mendiagnosis Salmonella typhi di Puskesmas Denpasar Timur 1 - Melania Antonia Barreto Cerqueira; Ni Nyoman Mahartini; I Wayan Putu Sutirta Yasa (Intisari Sains Medis, 2019)
Introduction: Typhoid fever is an acute systemic infectious disease caused by Salmonella typhi which is still widely found in various developing countries, especially in the tropics and subtropics. Widal test is an agglutination reaction between antigen and S. typhi O titer antibodies> 1/160 and S. typhi H titer >1/160, Aglutinin that is specific to Salmonella typhi in the serum of patients with typhoid fever.Methods: This research was descriptive observational cross sectional. The population of the study was patients from the East Denpasar Health Center 1 who presented with clinical symptoms that supported.Result: There were 10 sample (30%) aged 0-10 years, 12 sample (36%) people aged 11-20 years, 7 sample (21%) aged 21-30 years, and 4 sample (12%) people aged >30 year. Samples with clinical symptoms of fever> 37 ° C with digestive disorders (nausea, vomiting, abdominal pain) with or without impaired consciousness were 18 samples (55%). Samples with clinical symptoms of fever> 37 ° C with digestive tract disorders were 11 samples (33%). Samples with fever> 37 ° C were 4 samples (12%)Conclusion: There were 3% of positive widal test and 97% of negative widal test in the East Denpasar Health Center 1.Latar Belakang: Demam tifoid merupakan suatu penyakit infeksi akut sistemik yang disebabkan oleh Salmonella typhi yang masih dijumpai secara luas di berbagai negara berkembang terutama di daerah tropis dan subtropics. Uji Widal adalah suatu reaksi aglutinasi antara antigen dan antibody S. typhi O titer > 1/160 dan S. typhi H titer >1/160, Aglutinin yang spesifik  terhadap  Salmonella  typhi  terhadap dalam serum penderita demam  tifoid.Metode: Penelitian ini bersifat observasional cross sectional deskriptif Populasi Penelitian adalah pasien dari Puskesmas Denpasar Timur 1 datang dengan gejala klinis yang mendukung.Hasil: Rentang usia dari 33 pasien subjek penelitian, terdapat 10 sampel(30%) berusia 0 – 10 tahun, 12 sampel  (36 %) sampel berusia 11 – 20 tahun, 7 sampel (21%) berusia 21-30 tahun,  dan 4 sampel  (12 %) sampel berusia > 30 tahun. Sampel dengan gejala klinis demam > 37 °C dengan gangguan pencernaan (mual, muntah, nyeri perut) dengan atau tanpa gangguan kesadaran sebanyak 18 sampel (55%). Sampel dengan gejala klinis demam > 37°C dengan gangguan saluran pencernaan sebanyak 11 sampel (33%). Sampel dengan demam >37°C sebanyak 4 sampel (12%)Simpulan: Terdapat 3% sampel dengan widal positif dan 97% sampel dengan widal negatif di Puskesmas Denpasar Timur 1.